From Creativity to Success via Risk and Setback: Can you disrupt without disrupting? - Bandler, John (Bandler Corporation, 2023)
Creativity, innovation, entrepreneurship. These days, touted by researcher and administrator alike. But what leads to success? What portends failure? Imagination, facilities, opportunity, leadership, naïveté, hindsight, IQ, charm, favors, money, packaging, branding, humility, aggressiveness, or perhaps simply good luck: what roles do they play? Can you disrupt without disrupting? How have my views on academia, creativity, risk, entrepreneurship, and personal and professional advancement evolved in the decade since I initiated this lecture? Come and find out.
Presentation given by John Bandler as part of the ECE Distinguished Research Lecture Series, Department of Electrical and Computer Engineering, McMaster University, Hamilton, ON, Canada, Feb. 6, 2023. This material is based a series of prior presentations, in particular Bandler’s 2013 presentation From Creativity to Success via Risk and Setback, available on YouTube https://www.youtube.com/watch?v=wYOrhiN3NCU
Keywords: creativity; innovation; imagination; disruptive technology; breakthrough; entrepreneurship; branding; luck; perception; risk; fear; setback; professional advancement; truth; ethics; ridicule; first impressions; subtext; false praise; hidden agendas; pitching; elevator pitch; snow job; metrics; theatricality; story; persuasion; authenticity; fraud; corporate failures; science communication